OPTICAL RADIATION FROM THE SPUTTERED SPECIES UNDER EXCITATION OF TERNARY MIXTURES OF NOBLE GASES BY THE 6LI(N,Α)3H NUCLEAR REACTION PRODUCTS - Samarkhanov, K.; Khasenov, M.; Batyrbekov, E.; Gordienko, Yu.; Baklanova, Yu.; Kenzhina, I.; Tulubayev, Ye.; Karambayeva, I. (EURASIAN CHEMICO-TECHNOLOGICAL JOURNAL, 2021)
The present paper examines the luminescence of ternary Ar-Kr-Xe and Ne-Ar-Kr mixtures of noble gases in the spectral range from 300 to 970 nm, excited by the 6Li(n,α)3H nuclear reaction products in the core of a nuclear reactor. A thin layer of lithium applied on the walls of the experimental device, stabilized in the matrix of the capillary-porous structure, serves as a source of gas excitation. During in-pile tests, conducted at the IVG.1M research reactor, thermal neutrons interact via the 6Li(n,α)3H reaction, and the emergent alpha particles with a kinetic energy of 2.05 MeV and tritium ions with a kinetic energy of 2.73 MeV excite gaseous medium. The study was carried out in a wide temperature range. The temperature dependence of the intensity of the emission of the atoms of noble gases and alkali metals, heteronuclear ionic molecules of noble gases were studied. The obtained values of the activation energy of the emission process 1.58 eV for lithium and 0.72 eV for potassium agree well with the known values of evaporation energy. Excitation of alkali metals atoms occurs consequently of the Penning process of alkali metals atoms on noble gas atoms in the 1s-states and further ion-molecular reactions.
Keywords: Type of access: Open Access; nuclear reaction; sputtering; noble gases; alkali metals; level population